On the Colombian longhorned beetles (Coleoptera: Cerambycidae): A new species and new distribution records - Diaz, Sebastian Quimbayo; Bacca, Tito; Taboada-Verona, Carlos; Nearns, Eugenio H.; Lanuza-Garay, Alfredo (Zootaxa, 2025)
A new species of Colobothea (Lamiinae: Colobotheini), Colobothea carlosi sp. nov. is described from Colombia. Five new country records for Colombia are provided: Callichroma gounellei Achard, 1910; Lagocheirus araneiformis parvulus Casey, 1913; Leptostylus batesi Casey, 1913; Steirastoma lituratum Bates, 1885 and Sangaris ordinale Monné & Monné, 2009. Additionally, 30 new departmental records are provided, expanding the geographical distribution knowledge for the department of Sucre on the Caribbean side of Colombia.